Distribution and abundance of bat assemblages among different forest covers in Gorgona National Natural Park, Colombia - Murillo-García, Oscar Enrique (2014)
Bats are important for maintenance of ecological processes in tropical forests since they are among the most abundant mammals and play a crucial role in tropical succession. Due to the importance of bats to forest dynamics and to the lack of ecological information, a study was conducted to quantify the variation in species richness, abundance and occurrence of bats in forest with different levels of perturbation in Gorgona National Natural Park; accounting for imperfect detectability. Bats were captured with mist-nets in three areas that differed in their perturbation levels (2 sites per area). A total of 670 bats representing 10 species and three families (Emballonuridae, Phyllostomidae y Vespertilionidae) were captured. The frugivorous species Dermanura rosenbergi (44.1%), Carollia brevicauda (20.9%) and Artibeus lituratus (30.1%) were the most captured species, and 6 out of 10 were insectivorous. Detection probability (p) increased with the increase in perturbation level (pperturbed>psecondary>pprimary), and was highest for frugivorous bats. The best model for occurrence (Ψ) revealed that probabilities of occurrence increased with perturbation levels (Ψperturbed>Ψsecondary>Ψprimary) and differed among species. Substantial differences in abundance were due to an additive effect of perturbation level, body size, and guild. Abundance increased with perturbation level (Nperturbed>Nsecondary>Nprimary), decreased with body size, and was highest for frugivorous bats. Bats had higher occurrence and abundance values in most disturbed areas, but they also occurred in less disturbed areas. Consequently, bats can potentially eat fruits from different stages of succession, promoting seed movement among zones that are suitable for colonization. Bats should be considered a conservation target for Gorgona. Rev. Biol. Trop. 62 (Suppl. 1): 419-434. Epub 2014 February 01.